Metode Penafsiran Ibn al-‘Arabî dalam Ahkâm al-Qur’ân - Fahmi, Saiful (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2013)
This paper will explain the concept of ontological Ibn al-‘Arabi of interpretation, the general idea of the book Ahkâm al-Qur’ân that includes methods, patterns, sources of interpretation, interpretation elements and characteristics that distinguish it from the interpreters other. Ontological view regarding the interpretation that was never a logical consequence of the importance of the final carry was critical of the existing interpretation of the results so far, so it is legitimate to question whether Ahkâm al-Qur’ân is still relevant to the demands of his time or not? Whether in it there is coercion-coercion and preconceptions-ideological Ibn al-‘Arabî or not? Given, Ahkâm al-Qur’ân is reproduced in the 5th century AH, where the fight discourse between the schools of thought Islam was at its height. While Ibn al-‘Arabi is an intellectual who embrace genuine Mâlikî School, so it brought the prejudice that he is stuck in an ideological reason